(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
Studied the effect of various treatments of drip irrigation (60% PE, 80% PE, 100% PE and 120% PE) and sulphur (Control, 15 kg S ha-1, 30 kg S ha-1 and 45 kg S ha-1) on yield and economics of radish. Among the treatments, the drip irrigation at 100% PE was comparable to 120% PE, yielding the highest root fresh weight (213.09 g), root diameter (4.12 cm), root length (30.11 cm), total fresh weight per plant (291.05 g), yield per hectare (313.93 q ha-1), net returns (₹ 112,969 ha-1), and B:C ratio (3.57). Application of 30 kg S ha-1 resulted in maximum root fresh weight (211.75 g), root length (28.94 cm), and root diameter (3.98 cm), as well as the highest total fresh weight per plant (289.87 g), yield (301.57 q ha-1), and net returns (₹ 106,248 ha-1). The treatment combination of 100% PE irrigation with 30 kg S ha-1 resulted in the highest yield per hectare (331.21 q ha-1), though it was statistically comparable to the treatments of 100% PE with 45 kg S ha-1, 120% PE with 30 kg S ha-1, and 120% PE with 45 kg S ha-1.